Audit Quality Moderates the Effect of Independent Commissioners, Audit Committee, and Whistleblowing System on the Integrity of Financial Statement - Srikandhi, Mutia Femila; Suryandari, Dhini (Accounting Analysis Journal, 2020)
This study aims to analyze the moderation effect of audit quality on the relationship of independent commissioners, audit committee, and whistleblowing system on the integrity of financial statements. The population used State-owned companies listed on the IDX during 2014-2018. The sampling method used purposive sampling which produced 18 companies. The study used logistic regression and MRA through SPSS 23. The study results showed that independent commissioners and whistleblowing systems do not influence the integrity of financial statements. On the contrary, there is a significant positive effect of the audit committee. Audit quality moderates the relationship of independent commissioners on the integrity of financial statements. On the contrary, it does not moderate the audit committee and whistleblowing system variables. The conclusions of this study are there is a significant positive effect between the audit committee and the integrity of financial statements while there is no effect of independent commissioners or whistleblowing system on the integrity of financial statements. Audit quality strengthens the relationship of independent commissioner on the integrity of financial statements but it is unable to moderate the relationship of the audit committee and whistleblowing system on the integrity of financial statements. The absence of research using the whistleblowing system variable as the independent variable on the integrity component of financial statements makes it an important study to be examined. Keywords: Integrity of financial statements; Independent Commissioners; Audit Committees; Whistleblowing System; Audit Quality